Potential Links Between Certified Organic Coffee and Deforestation in a Protected Area in Chiapas, Mexico. (February 2016) - Jurjonas, Matthew; Crossman, Katie; Solomon, Jennifer; Baez, Walter Lopez
Highlights: A producer survey and interviews were conducted on coffee production in Chiapas, Mexico. Organic coffee producers have an economic edge from price premiums and comparable yields. Land reform and shifting cultivation have created a complex history of land use change. Organic coffee certification inspections do not create a baseline for measuring deforestation. Collaborative management and streamlining inspections are necessary to prevent deforestation. Summary: This study considers organic coffee certification and deforestation in the El Triunfo Biosphere Reserve of Chiapas, Mexico. Land reform, dating back to the revolution, has created a complex context for measuring land use change. The locally improved price of organic production, maintained yield, and plantation growth rate—twice that of conventional producers—raise questions about potential deforestation. While consumers believe organic does not deforest, no measurements are taken during inspection. As communal land privatizes without an established baseline for land use change, improved organic certification inspections are needed to verify good practices and advance forest conservation in the coffee sector.